106k views
0 votes
. Use trigonometric expressions to build an equivalent trigonometric identity with the given expression: cos (x) − cos3 (x) = ?

A)cos (x) sin (x)
B)cos (x) sin2 (x)
C)sin2 (x)
D)sin (x) cos2 (x)

1 Answer

4 votes

Answer:

B

Explanation:

We want to determine an equivalent trignometric identity with the given expression:


\cos (x) - \cos^3 (x)

We can factor out a cos(x):


=\cos (x) (1-\cos^2 (x))

Recall from the Pythagorean Identity that:


\sin^2(x) + \cos^2(x) = 1

Therefore:


\displaystyle \sin^2(x) = 1 - \cos^2(x)

Substitute:


=\cos(x)(\sin^2(x))=\cos(x)\sin^2(x)

Our answer is B.

User Paul Van Jaarsveld
by
5.6k points